PENGARUH WARNA BAGI PENIKMAT FOTOGRAFI LANSKAP - Tony Kurniawan (ARTic, 2018)
Landscape photography started with black and white photos. There is a tradition of landscape photography that began more than 150 years ago. At the time, the photographer using film that is very slow and very less sensitivity. So the landscape becomes a perfect subject for a photograph. The reason is because the landscape is not moving during the long exposure. At that time also for landscape photography became a way to discover and explore the world. Landscape photography strange turn at the beginning of the 1900s when photographers think they should be like a painter and create an image that does not look too real. Up until now photography landscape continues to evolve. This raises the serious effect of the emergence of different representations of landscape photography. Based on these problems researchers conducted the study by dissecting photos - landscape both color and black and white of the few photographers in Indonesia with using visual analysis (composition, light, color, etc.). Based on visual analysis of some landscape color and black and white photos found several factors that influence the weather and light and dark colors, the experience and knowledge of the photographer affects the photo. Representation of a landscape photo color is affected by color. Chartreuse colors - brass provides warmth while -biruan bluish color gives the impression of cold. Landscape photography in black and white are displayed with more talk about sharpness, detail and atmosphere that feels somewhere. black and white landscape photography represents nature becomes visible not too real. Photo black and white landscape provide opportunities for photo connoisseurs imagination. Photography landscape aesthetics and beauty because the photographer as creator photograph to enter the spirit of adventure, self-expression and even culture in the work.